Investigating Effects of the Flipped Classroom on the Development of Inferential reading comprehension - NAKKAM, Jillali; Jmila , Malika (International Journal of Language and Literary Studies, 2024)
The present study aims to investigate effects of the flipped classroom on the development of inferential comprehension at Ibn Tofail University. It also explores students’ perceptions of this innovative model. It is worth noting that research on the correlation between the flipped model and inferential comprehension at the university level remains exceedingly limited, not only in the context of Morocco but also in similar research environments. The study employs a quasi-experimental mixed method design, specifically an explanatory sequential approach. In the initial phase, pre- and post-reading comprehension tests are performed to compare the flipped and non-flipped classrooms for any significant differences. In the second phase, a semi-structured interview is carried out to examine students' perceptions of the flipped model. The study comprised 81 undergraduate semester one students from the English department, divided into experimental and control groups. The post-test results have showcased statistically significant advantages in favour of the experimental group. The qualitative results have revealed that the interviewees expressed positive opinions about this innovative teaching model. In conclusion, this study suggests that the flipped model may create a conducive environment for students to actively participate in discussions, engage in critical thinking, and solve problems.